Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/jez.b.23019
|View full text |Cite
|
Sign up to set email alerts
|

The phylogenetic position of Arhaphe deviatica within Hemipteran insects: A potential model species for eco‐devo studies of symbiosis

Abstract: Insecta is known to be the most diverse group of species, exhibiting numerous forms of endosymbiotic associations. Molecular techniques have provided significant indicators for insect–microbe interactions. The present study aimed to register one of the true bugs of pentatomomorpha and clarify its taxonomic position through phylogenetic analysis of the partial 16S rRNA gene region. A maximum likelihood analysis retrieved a generally well‐supported phylogeny based on Tamura 3‐parameter model. Based on the partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Thus, it can be concluded that DNA barcoding was useful for investigating true bug species [45]. This study is limited to related species because of nucleotide substitution [46]. Mitochondrial DNA was also useful in the identification of true bugs like Indian Pentatomid.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Thus, it can be concluded that DNA barcoding was useful for investigating true bug species [45]. This study is limited to related species because of nucleotide substitution [46]. Mitochondrial DNA was also useful in the identification of true bugs like Indian Pentatomid.…”
Section: Phylogenetic Analysismentioning
confidence: 99%